Long time clinical course of cardiac sarcoidosis with corticosteroid therapy -from Japanese nationwide questionnaire survey-. (25th November 2020) - Kamada, H; Ishibashi, K; Nakajima, K; Ueda, N; Kamakura, T; Wada, M; Yamagata, K; Inoue, Y; Miyamoto, K; Nagase, S; Noda, T; Aiba, T; et al.
Abstract: Background: Sarcoidosis is a systemic inflammatory syndrome of unknown etiology and cardiac involvement has been reported to be an important prognostic factor in this disease. An autopsy study has reported that the frequency of this cardiac involvement (cardiac sarcoidosis: CS) varies in the different countries and races and very frequent in Japanese patients. We therefore performed the nationwide questionnaire survey and try to clarify the clinical characteristics and corticosteroid effect in CS, especially focused on arrhythmic events in this disease. Methods: Total of 757 Japanese patients from 57 hospitals who diagnosed CS were examined. Patients who unsatisfied the criteria of the Japanese new guidelines, or who underwent cardiac transplantations were excluded, and 420 patients (287 females, median follow-up periods 1864 days [interquartile range: 845–3159 days]) were analyzed. The clinical outcome and corticosteroid effect were evaluated. Results: Clinical characteristics at diagnosis was as follows: female dominant (68%), mean age of 60±13 years old, mean left ventricular ejection fraction was 49±16%. Arrhythmic events were very frequently observed as an initial cardiac manifestation in 263 patients (62%) of CS, of which atrioventricular block (AVB) in 174 (41%), ventricular tachycardia (VT) in 73 (17%) and AVB with VT in 17 (4%) (Figure 1A). Pacemaker was implanted in 166 patients (40%) and defibrillators was 137 patients (33%). Corticosteroid was prescribed in 144 (83%) of 174 patients with AVB and in 62 (85%) of 73 patients with VT. Initial dose was mean 47.9 mg and maintenance dose of mean 7.3 mg. Corticosteroid improved VT as good as AVB (27% vs. 29%). However, corticosteroid sometimes worsened VT events compared with AVB (10% vs. 2%) (Figure 1B). During the course of follow-up, 32 patients were needed to increase corticosteroid in 23 of AVB and 10 of VT cases. However, there were no difference in mortality between the groups, whether or not to increase corticosteroid. All survival rate was 92% (5-year mortality), 83% (10-year mortality) and free from all cause death and defibrillator charge was 81% (5 year), 71% (10 year). Conclusion: Fatal arrhythmia is commonly observed in CS as a primary symptom. Corticosteroid sometimes worsen ventricular arrhythmia and appropriate defibrillator discharge was common. Thus, careful attention for activating ventricular arrhythmia would be needed during the follow-up period even after corticosteroid therapy. Funding Acknowledgement: Type of funding source: None